Experimental investigation of palm oil methyl ester nanofluid as a liquid insulating material - Yusri Jumat; Yanuar Z. Arief; Hendri Masdi; Valentine M. A. A. Jabu; Sharifah M. W. Masra; Nurul I. Hashim; S. K. Sahari; N. Junaidi; S. Rufus; Hamzah Eteruddin; Sinka Wilyanti (Teknomekanik, 2026)
This study evaluates Palm Oil Methyl Ester (POME) as a potential base fluid for transformer insulation, enhanced with Titanium Dioxide (TiO₂) nanoparticles. The research aims to assess the dielectric strength and physicochemical properties of TiO₂-POME nanofluids at two concentrations (0.05 g/L and 0.10 g/L) and compare them with pure POME. The breakdown voltage (BDV) test was conducted before and after thermal ageing to determine how the nanofluid's dielectric strength changes over time. Results showed that both nanofluid samples had higher BDV values than pure POME, with the 0.05 g/L sample increasing from 19.27 kV to 25.85 kV and the 0.10 g/L sample showing the most significant improvement, with a BDV of 33.17 kV. Ageing caused a slight decrease in BDV, but the values remained higher than those of the base fluid (15.40 kV for aged pure POME), with the 0.05 g/L and 0.10 g/L samples maintaining averages of 20.68 kV and 24.44 kV, respectively, suggesting improved insulation performance. The kinematic viscosity of pure POME was 8.85 cSt, while the 0.05 g/L and 0.10 g/L TiO₂ nanofluids showed values of 9.09 cSt and 9.52 cSt, respectively, with all the samples falling within the acceptable range of 3-12 cSt specified by IEC 60296 for transformer insulating oils. The addition of TiO₂ slightly increased viscosity, more noticeably at 0.10 g/L. FTIR analysis indicated that the chemical structure of the fluid remained stable after ageing and nanoparticle addition.